Pengaruh Risiko Sistematis, Market Timing, dan Ukuran Dana Terhadap Kinerja Reksa Dana Pendapatan Tetap Syariah di Indonesia (Periode 2014-2018) - Febrita Kusumastiti; Muhammad Nafik Hadi Ryandono (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
The purpose of this study is to determine the effect of the systematic of risk, market timing, and fund size toward sharia fixed income mutual funds in Indonesia period 2014-2018 partially and simultaneously. This research uses a quantitative approach and uses multiple linear regression tests to determine the relationship between exogenous variables and endogenous variable. The result of this research shows that systematic risk and fund size are partially have significant influence to the sharia fixed income mutual funds performance. Meanwhile, market timing is partially have insignificant influence to the sharia fixed income mutual funds performance. While simultaneously, systematic risk, market timing and fund size have significant influence to the sharia fixed income mutual funds performance with the coefficient of determination is 31,9% while the remaining 68,1% is influenced by other variables not included in this research.Keywords: Sharia Mutual Fund Performance, Systematic Risk, Market Timing, Fund Size